1981
DOI: 10.1177/000331978103200204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manual Lymphdrainage Massage on Blood Components and Urinary Neurogormones in Chronic Lymphedema

Abstract: In an earlier paper we have shown that manual lymph drainage massage of edematous limbs can result in the excretion of up to 1 liter urine derived from reabsorption and transport from the interstitial fluid, simultaneously with significant changes in the excretion of urinary neurohormones. These findings indicated that histamine and serotonin were released from the edematous tissue and that circulation improved through increased output of adrenaline and noradrenaline. The results achieved led us to assume that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…MLD therapy is used to improve lymph flow in the lymphatic system and to discharge metabolites into the circulatory system and then into the excretory system [ 30 , 31 ]. MLD therapy can also stimulate the flow of nutrients transported through the blood to the tissues, as well as improve the metabolism of adipose tissue and the drainage of metabolic products [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…MLD therapy is used to improve lymph flow in the lymphatic system and to discharge metabolites into the circulatory system and then into the excretory system [ 30 , 31 ]. MLD therapy can also stimulate the flow of nutrients transported through the blood to the tissues, as well as improve the metabolism of adipose tissue and the drainage of metabolic products [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kurz et al 21 found changes in excretion of urinary neurohormones, specifically significant increases in histamine and serotonin, immediately following MLD in patients with lymphedema whereas no changes were found in healthy controls post-MLD. 21,22 In a pilot study, Tan et al. 23 reported near-infrared fluorescence imaging visualized lymphatic contractility improvements with an increase in both lymph velocity and propulsive frequencies immediately post-MLD for the involved and contralateral limbs in patients with known lymphedema and in both limbs of healthy controls.…”
Section: Quantitative Changes After Mldmentioning
confidence: 99%